Public discourses and government interventions behind China’s ambitious carbon neutrality goal - Fang Zhang; Manchi Xu; Yikuan Yan; Keman Huang (Communications Earth & Environment, 2023)
Abstract Mobilizing the public supports on ambitious climate change goals is crucial for climate action. Here we examine what public discourses have emerged in China around its ambitious carbon neutrality goal and how Chinese government has influenced its public opinion. By using deep learning model to analyze approximately one million microblogs from China, we track the evolution of seven climate discourses among the online public discussing China’s carbon neutrality goal, including scientific, moral, economic, co-benefit, energy security, political, and global frames. Among this community, we find a high level of supports towards China’s carbon neutrality goal. Opposers cite global and moral concerns as their main reason for opposition and are increasingly internally divided in China. Those who are neutral are more easily influenced by an economic discourse. Major climate policies are more effective than politics to influence public views on carbon neutrality.